Zn(II)-bis(cyclen) complexes and the imaging of apoptosis/necrosis - Oltmanns, Dörte; Zitzmann-Kolbe, Sabine; Mueller, Andre; Bauder-Wüst, Ulrike; Schaefer, Martin; Eder, Matthias; Haberkorn, Uwe; Eisenhut, Michael (Bioconjugate chemistry, 2011)
In vivo cell-death imaging is still a challenging issue. Until now, only 99mTc-labeled HYNIC-rh-annexin A5 has been extensively studied in clinical trials. In the ongoing search for an alternative imaging agent, we synthesized a series of fluorescent zinc-cyclen complexes as annexin A5 mimics and studied structural variations on the uptake behavior of cells undergoing apoptosis/necrosis. The number of cyclen chelators was varied and the spacer separating cyclen from the central scaffold was modified. Five zinc-cyclen complexes were labeled with fluorescein for flow cytometric studies and one was labeled with 18F for in vivo applications. Jurkat cells were treated with staurosporine to induce apoptosis/necrosis, incubated with the fluorescein-labeled zinc complexes and analyzed them by flow cytometry. Fluorescent annexin A5 and propidium iodide were applied as reference dyes. Flow cytometry revealed greater accumulation of zinc-cyclen complexes in staurosporine treated cells. The uptake was contingent on the presence of zinc and the fluorescence intensity was dependent on the number of zinc-cyclen groups. Confocal laser scanning microscopy showed the {bis[Zn(cyclen)]}4+ complex distributed throughout the cytosol different to annexin A5. Owing to the structural similarity of the bis-cyclen ligands with CXCR4 binding bis-cyclam derivatives the zinc-cyclen complex uptake was challenged with the meta derivative of AMD3100. Lack of uptake depletion in staurosporine treated cells ruled out measurable CXCR4 interaction. PET imaging using the 18F labeled zinc-cyclen complex revealed significantly higher uptake in an irradiated Dunning R3327-AT1 prostate tumor as compared to the contralateral control tumor. PET imaging of a HelaMatu tumor model additionally showed an increased uptake after taxol treatment. It could be demonstrated that the fluorescent zinc-cyclen complexes offer potential as new agents for flow cytometry and microscopic imaging of cell death. In addition, the 18F labeled analogue holds promise for in vivo applications providing informations about cell death after radiation therapy and cytostatic drug treatment.